Utilization of Yard Land for Cultivation of Environmentally Friendly Medicinal Plants in Banjarwaru Village, Gilangharjo, Pandak, Bantul - Wahid, Rahmat A Hi; Purwaningsih, Okti (LPPM UIKA Bogor, 2024)
Food security will have an impact on the main problems in most countries in the world due to the increasing population, increasing purchasing power and global climate dynamics. Efforts to build family food security, one of which can be done by utilizing available resources, including through the utilization of yard land through family medicinal plants (TOGA). Based on the results of educational counseling activities and discussions, it can be concluded that most residents agree on the benefits and importance of TOGA and cultivation techniques correctly in their yards, especially in Banjarwaru Hamlet, Gilangharjo Village, Pandak District, Bantul, Yogyakarta.